Examination of early treatment effects and related biases during the conduct of two UK-wide pragmatic orthopaedic surgical trials: ProFHER and UK FROST. (21st February 2023) - Knowlson, Catherine N.; Brealey, Stephen; Keding, Ada; Torgerson, David; Rangan, Amar
Abstract : Aims: Early large treatment effects can arise in small studies, which lessen as more data accumulate. This study aimed to retrospectively examine whether early treatment effects occurred for two multicentre orthopaedic randomized controlled trials (RCTs) and explore biases related to this. Methods: Included RCTs were ProFHER (PROximal Fracture of the Humerus: Evaluation by Randomisation), a two-arm study of surgery versus non-surgical treatment for proximal humerus fractures, and UK FROST (United Kingdom Frozen Shoulder Trial), a three-arm study of two surgical and one non-surgical treatment for frozen shoulder. To determine whether early treatment effects were present, the primary outcome of Oxford Shoulder Score (OSS) was compared on forest plots for: the chief investigator's (CI) site to the remaining sites, the first five sites opened to the other sites, and patients grouped in quintiles by randomization date. Potential for bias was assessed by comparing mean age and proportion of patients with indicators of poor outcome between included and excluded/non-consenting participants. Results: No bias in treatment effect was observed overall for the CI site, or the first five sites, compared with the remaining sites in either trial. An early treatment effect on the OSS was observed for the first quintile of participants recruited to ProFHER only (clinically relevant difference of seven points). Selection bias for age was observed in the ProFHER trial only, with slightly younger patients being recruited into the study. Both trials showed some selection bias for markers of poor prognosis, although these did not appear to change over time. Conclusion: No bias in treatment effects overall were found at the CI or early sites set-up. An early treatment effect was found in one of the two trials, which was likely a chance effect as this did not continue during the study. Selection bias was observed in both RCTs, however this was minimal and did not impact on outcome. Cite this article: Bone Jt Open  2023;4(2):96–103.